EPIDEMIOLOGICAL PROFILE OF DENGUE IN NORTHEASTERN BRAZIL FROM 2014 TO 2024 - Ribeiro, Nayara Fernanda Amorim Madeiros; da Silva, Alicia Malaquias; Barros, Rafael Almeida; dos Santos, Pedro Julio Corado Carneiro; Cavalcante, José Gabriell Feitosa; de Almeida, Ana Carolina Medeiros (Seven Editora, 2024)
Dengue, transmitted by the Aedes aegypti mosquito, is a serious public health challenge, especially in the Northeast of Brazil, due to social vulnerability and climatic conditions favorable to the proliferation of the mosquito. Between 2014 and 2024, more than 10 million cases were recorded. This is a retrospective study with an epidemiological aspect that aimed to describe the epidemiological profile of dengue in the Brazilian Northeast from 2014 to 2024. Methodology: The selected variables were obtained through the Notifiable Diseases Information System (SINAN). A comparison was made between the years and the descriptive analysis of the data.  Results: Thus, it is observed that SINAN data indicate that the states of the Northeast have a significant contribution to the persistence of the epidemic, with Bahia registering the highest number of cases in four consecutive years. Most infections occurred in people with incomplete elementary school and in the age group of 15 to 39 years. The brown race was the most affected and the female sex had the highest number of notifications. Conclusion: Dengue remains a serious public health problem in Brazil, especially in the Northeast, due to disorderly urbanization, hot climate, and unsanitary conditions. It is crucial to strengthen public policies to improve sanitation, awareness, diagnosis, treatment and vaccination. DOI:https://doi.org/10.56238/sevened2024.037-063